Pengaruh Komitmen dan Kinerja Manajemen Koperasi terhadap Kepuasan Anggota Melalui Kualitas Pelayanan sebagai Intervening - Teti Safari (Jurnal Ilmiah Aset, 2020)
The purpose of this study was to analyze the commitment and performance of cooperative management on member satisfaction through service quality. The research subjects were commissioner members, sample 73, sampling technique with purposive sampling. Data collection techniques through questionnaires, data analysis techniques with SmartPLS. The results of the study (1) Commitment variable has a positive and significant effect on service quality, the parameter coefficient value is 0.489 with a P-Value of 0,000. (2) Employee performance Variable has a positive and significant effect on service quality with a coefficient value of 0.461 with a P-Value of 0,000. (3) Commitment variable has a positive effect on job satisfaction, parameter coefficient value of 0.314 with P-Value 0.001. (4) Employee performance variable has no positive and significant effect on member satisfaction, parameter coefficient value of 0.037 with P-value of 0.530. (5) Variable quality has a positive and significant effect on member satisfaction, parameter coefficient value 0.742 with a P-value of 0.000.